(untitled) (Nexo Revista Científica, 2021)
Significant oil losses in oil-containing wastes and their adverse impact on the region’s environmental setting bring about the need to develop an oil-containing wastes treatment technology. To tackle this issue, the authors have set an aim of designing a helio device and creating an oil-containing wastes treatment method based on it to extract oil products. Considering a wide spread in the composition and properties of potential oil sludge raw materials and their tendency for either formation of stable emulsions or phase separation, we have conducted in-depth modern physical and chemical studies and defined the need to develop a commercial oil-containing wastes purification method. We have designed the device, in which oil product hydrocarbons undergo thermal treatment using solar energy without prejudice to their chemical structure. Following oil-containing wastes purification using solar energy, the particulate load in soil does not exceed 6.65-6.79% and the absolute molecular weight of hydrocarbons approaches that of bitumen. The oil-containing wastes purification method developed solves an important environmental issue of oil-containing wastes recycling, promotes recovery and prevents degradation of natural complexes, and reduces soil and water pollution.